Effects of formamidinium and bromide ion substitution in methylammonium lead triiodide toward high-performance perovskite solar cells - Yang, Zhibin; Chueh, Chu-Chen; Liang, Po-Wei; Crump, Michael; Lin, Francis; Zhu, Zonglong; Jen, Alex K.-Y. (Nano energy, 2016)
Compositional engineering of organic-inorganic hybrid perovskite has attracted great research interests recently for seeking a better perovskite system to address existed challenges, such as the thermal and moisture instability, anomalous hysteresis, and toxic lead contamination, etc. In this study, we systematically investigated the structural, optophysical, and photovoltaic properties of the compositional MAxFA1−xPb(IyBr1−y)3 perovskite by sequentially introducing FA+ and Br- ions into the parental MAPbI3 to elucidate their respective roles when they were inserted into the perovskite lattice. We unraveled that such dual compositional tuning in perovskite can improve the crystallinity of the resultant film and thus reduce its density of defect states as evidenced by admittance spectroscopy, resulting in a prolonged carrier lifetime over 500ns. As a result, a promising average PCE (PCEAVG) of 17.34% was realized in the optimized MA0.7FA0.3Pb(I0.9Br0.1)3-based PVSC with little hysteresis and stable photocurrent output. More significantly, another compositional MA0.7FA0.3Pb(I0.8Br0.2)3 perovskite with a large bandgap of 1.69eV can yield an impressively high PCEAVG over 15%. To the best of our knowledge, this performance is among the state-of-the-art large bandgap (~1.7eV) PVSCs reported so far, which paves the way for the development of high-performance tandem cells using efficient large bandgap PVSCs as the top subcells. This study not only manifests the pivotal roles of dual compositional tuning in MAxFA1−xPb(IyBr1−y)3 perovskites but also highlights the importance of compositional engineering for developing an even more efficient perovskite. The structural, optophysical, and photovoltaic properties of the compositional MAxFA1−xPb(IyBr1–y)3 perovskite were systematically studied by gradually introducting FA+ and Br− ions into the MAPbI3 to elucidate the roles of FA+ and Br− ions in the compositional perovskites. Benefitting from the improved thin-film crystallinity, prolonged carrier lifetime, and extended absorption introduced by such dual compositional engineering, a high average PCE of 17.34% was realized in the MA0.7FA0.3Pb(I0.9Br0.1)3-based solar cell. More importantly, the MA0.7FA0.3Pb(I0.8Br0.2)3 perovskite with a large bandgap of 1.69eV can exhibit a high PCE over 15%, which is among the state-of-the-art large bandgap (~1.7eV) PVSCs reported to date. [Display omitted] •The roles of FA+ and Br- ions in MAxFA1-xPb(IyBr1-y)3 perovskite were revealed.•An average PCE of 17.34% was realized in the optimized MA0.7FA0.3Pb(I0.9Br0.1)3-based PVSC.•A perovskite with a large bandgap of 1.69eV yields a high PCEAVG over 15%.